Assessment of Acrylamide Levels and Evaluation of Physical Attributes in Bread Made with Sourdough and Prolonged Fermentation - Lopez-Moreno, Cristina; Fernández-Palacios, Sara; Ramírez Márquez, Pedro; Ramírez Márquez, Salvador Jesús; Ramírez Montosa, Carlos; Carlos Otero, Juan; López Navarrete, Juan Teodomiro; Ponce Ortiz, Rocío; Ruíz Delgado, María Carmen (Food Science and Engineering, 2023)
Over the past decades, there has been an increasing awareness regarding acrylamide content in cooked foods. The use of natural, homemade, organic and ecological ingredients has been promoted in our society as a strategy to combat the increase in cancer ratios. In this work, the use of sourdough and prolonged fermentation as a mitigation of acrylamide formation in bread were studied. In addition, to accomplish the required standards of industrial production, the dimension and acidity were also assessed. For this purpose, samples were elaborated using diverse fermentation times (0, 60, 120, 180, 240, 300 and 360 minutes) of the dough before baking and different sourdough percentages (0, 20 and 50%). High-performance liquid chromatography/electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) method for acrylamide determination in bread crust was applied. We could corroborate that a decrease in acrylamide levels was observed with fermentation time for samples containing 0 and 20% sourdough, being sharper the decrease for the latter. However, the samples containing 50% sourdough showed a quite different behaviour depending on the fermentation time interval. The physical study revealed that dimension of the pieces increased with fermentation time and sourdough content, until the excessive gluten degradation and acidification of the medium led to a flattening and decrease in elevation of the samples. This study revealed that the samples containing a percentage of 20% sourdough maintained the proper quality of gluten for longer fermentation times than the 50% sourdough samples, delaying the flattening of the samples with fermentation time. Statistical calculations were accomplished in order to elucidate the correlations between the different variables, observing that the titratable index was associated with the fermentation time, the sourdough content, the bulk density and the acrylamide content.